THE INFLUENCE OF PRICE AND LOCATION ON INTEREST VISITING IN BETAWI RESTAURANT BABEH SADELI, PONDOK AREN, TANGERANG - Tri Djoko Sulistiyo; Pricilia Johani Sakti; Eduard Rudolf Pangkerego (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This research aims to determine the influence of price and location on interest in visiting the Betawi Babeh Sadeli Restaurant, Pondok Aren, Tangerang. This research is quantitative in nature using two types of data, namely primary data and secondary data obtained through observation and distributing questionnaires to consumers. Secondary data includes sources such as books, theses and previous research journals. The population of this research is consumers of the Betawi Babeh Sadeli Restaurant. The sampling technique used is Simple Random Sampling, with a random sampling technique called the Accidental Sampling technique. The samples taken were 100 respondents. Affordable prices and strategic location have a big influence on interest in visiting Betawi Babeh Sadeli Restaurant. Affordable prices make restaurants more accessible to various levels of society, while strategic locations make access easier and increase customer interest with a wider market reach.